2021
DOI: 10.1371/journal.pone.0252865
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Venturia inaequalis isolates (Apple scab) in China and U.K. determined by SSR markers

Abstract: Apple scab caused by Venturia inaequalis is a serious disease of cultivated apple worldwide. In this study, we collected 132 V. inaequalis isolates from Shaanxi, Gansu, Xinjiang, and the U.K. and analyzed their genetic diversity by using 13 microsatellite markers. Cluster analysis based on population structure and genetic distances suggested high similarity among the four regions. Population differentiation values ranged from 0.044 to 0.155, indicating there is a high level of kinship among the four regions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In this study, the AFLP molecular marker technique was used to analyze the genetic diversity of V. inaequalis from six different geographical regions of Gansu Province. The results showed that the populations of Jingning, Jingchuan, Lingtai, Maiji, Xifeng and Ning isolates were genetically similar and were consistent with the results of previous studies in China ( Hu et al, 2008 ; Fu et al, 2010a ; Li et al, 2021 ). The main environmental factors affecting the genetic variation of apples are the apple planting area and the pathogen hosts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the AFLP molecular marker technique was used to analyze the genetic diversity of V. inaequalis from six different geographical regions of Gansu Province. The results showed that the populations of Jingning, Jingchuan, Lingtai, Maiji, Xifeng and Ning isolates were genetically similar and were consistent with the results of previous studies in China ( Hu et al, 2008 ; Fu et al, 2010a ; Li et al, 2021 ). The main environmental factors affecting the genetic variation of apples are the apple planting area and the pathogen hosts.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, by utilizing SSR to analyze the genetic diversity of V. inaequalis populaces within the UK and China, the results showed that the genetic relationship between both regions was relatively close. This was because most of the apple dwarf seedlings planted in Northwest China were from the EM system in the UK ( Li et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and population structure of V. inaequalis has caught the attention of research groups in Europe and other regions for decades [ 10 , 13 , 15 , 31 ]. In contrast, in some regions only recently studies on the genetic diversity of this economically important pathogen have been carried out [ 9 , 18 , 42 ]. This study is the first report about V. inaequalis population diversity in Latvia based on the genotyping within twelve microsatellite loci.…”
Section: Discussionmentioning
confidence: 99%
“…The favourable weather conditions during the winter and spring in Latvia may positively affect annual sexual reproduction, thus resulting in higher genetic diversity within populations. In addition, the high diversity of cultivars may also have a significant differential selection pressure on V. inaequalis in orchards [ 14 , 42 ]. Our results were consistent with previous works [ 9 , 18 , 19 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation